Synthesis, crystal structure, and Hirshfeld surface analysis of a cubane-type tetranuclear polyoxotitanate cluster - Nath, Jayanta Kumar (European Journal of Chemistry, 2025)
A cubane-type tetranuclear polyoxotitanate cluster derived from 8-(isopropoxycarbonyl)-1-naphthoic acid is reported which is synthesized under reflux conditions in isopropanol (HOiPr). The ligand 8-(isopropoxycarbonyl)-1-naphthoic acid (INA) was generated in situ from 1,8-naphthalic anhydride and isopropyl alcohol in the reaction mixture where one of the carboxylate groups of 1,8-naphthalene dicarboxylic acid (generated from the ring opening reaction of 1,8-naphthalic anhydride) forms isopropyl ester by reacting with solvent isopropoxide. The solid-state structural elucidation of the cluster is achieved through the single crystal X-ray diffraction method, providing detailed insights into their molecular arrangements. Crystal data for C72H80O24Ti4: Triclinic, space group P-1 (no. 2), a = 19.086(3) Å, b = 20.341(4) Å, c = 21.538(4) Å, α = 88.895(4)°, β = 72.158(4)°, γ = 89.049(4)°, V = 7958(3) Å3, Z = 4, T = 293(2) K, μ(MoKα) = 0.457 mm-1, Dcalc = 1.269 g/cm3, 64356 reflections measured (4.42° ≤ 2Θ ≤ 54.94°), 34455 unique (Rint = 0.0458, Rsigma = 0.0752) which were used in all calculations. The final R1 was 0.0603 (>2sigma(I)) and wR2 was 0.1558 (all data). In the crystal lattice, the asymmetric unit of the cluster contains two molecules. Various types of supramolecular interactions such as C-H···O, C-H···π, π···π and unusual O···O interactions are observed in the X-ray structures. All these interactions guide the formation of 3D supramolecular architecture in the solid state of the compound. In addition to these, 2D fingerprint (2D-FP) and Hirshfeld surface analysis (HSA) computations were used to prove and quantify various supramolecular interactions within the crystal lattice.